2007
DOI: 10.1186/1471-2180-7-42
|View full text |Cite
|
Sign up to set email alerts
|

Indole is an inter-species biofilm signal mediated by SdiA

Abstract: Background: As a stationary phase signal, indole is secreted in large quantities into rich medium by Escherichia coli and has been shown to control several genes (e.g., astD, tnaB, gabT), multi-drug exporters, and the pathogenicity island of E. coli; however, its impact on biofilm formation has not been well-studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
478
2
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 411 publications
(513 citation statements)
references
References 65 publications
23
478
2
10
Order By: Relevance
“…2010). Several Gram‐positive and Gram‐negative bacteria synthesize indoles as intracellular signalling molecules to control the virulence of pathogenic bacteria, such as, Pseudomonas aeruginosa and enterohaemorrhagic E. coli O157:H7 (Lee et al ., 2007, 2011). In Pseudomonas putida , signalling molecules such as indole enhances TtgGHI efflux pump that are relevant for antibiotic resistance (Molina‐Santiago et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…2010). Several Gram‐positive and Gram‐negative bacteria synthesize indoles as intracellular signalling molecules to control the virulence of pathogenic bacteria, such as, Pseudomonas aeruginosa and enterohaemorrhagic E. coli O157:H7 (Lee et al ., 2007, 2011). In Pseudomonas putida , signalling molecules such as indole enhances TtgGHI efflux pump that are relevant for antibiotic resistance (Molina‐Santiago et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…S. typhimurium and E. coli have a luxR homolog called sdiA, but do not produce any detectable AHLs (Wang et al, 1991;Smith and Ahmer, 2003). Importantly, SdiA has been shown to respond to exogenous AHLs and regulate virulence in S. typhimurium and biofilm formation in E. coli (Wang et al, 1991;Smith and Ahmer, 2003;Lee et al, 2007); both phenotypes are important for competition and host interactions.…”
Section: Incomplete Qs Circuitsmentioning
confidence: 99%
“…For example, Pseudomonas aeruginosa contains two QS circuits (LasI/R and RhlI/R) but also contains QscR and a fourth LuxR-type protein identified here ( Figure 1b). It has been suggested that these extra LuxR-type proteins are orphans (Fuqua, 2006); however, as they belong to a characterized protein family (AHL response regulators) and the biological role of several has been described (Wang et al, 1991;Smith and Ahmer, 2003; Lee et al, 2006Lee et al, , 2007Lequette et al, 2006), they cannot be considered orphans. The best-characterized of these extra LuxR-type proteins in a bacterium with complete QS circuits is BisR in Rhizobium leguminosarum bv.…”
Section: Extra Luxr-type Proteinsmentioning
confidence: 99%
“…One recently-characterized metabolite biofilm signal is indole, which represses biofilm formation of E. coli by repressing motility, inducing the sensor of the quorum-sensing signal autoinducer-1 and influencing acid resistance (Lee et al, 2007b). A series of genes including bssR/bssS, bhsA and ariR have been identified as regulating biofilm formation through indole (Domka et al, 2006;Lee et al, 2007c;Zhang et al, 2007), and hydroxy indoles have been shown to be signals for pathogenic E. coli Lee et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%